Analysis of Violations of the Advertising Code of Ethics in Advertising Spotify “Listening Is Everything” - Ismianti, Rahma; Putri, Elmalia; Lutfia, Ashri; KN, Jamiati (PT Literasi Nusantara Publisher, 2023)
As the development of media and technology has placed it as the leading media in transformation and communication, advertising has also increased, one of which is in advertisements that air through TVC media. Spotify is a company that makes advertisements through TVC with the title